Why reading matters - Carter, Rita. (Hamilton, NJ : Films for the Humanities & Sciences, 2010)
This program seeks to understand how the brain, which has evolved no hardwired 'reading center,' made the leap to literacy.
Presenter, Rita Carter.
Keywords: Literacy; Neurolinguistics; Reading